Pengaruh Diskon dan Gratis Ongkos Kirim Terhadap Keputusan Pembelian Pada Pengguna Tiktok Shop di Kota Makassar - Ni Made Sri Utami Dwiyanti; Kerta Widana (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the effect of discounts and free shipping on purchasing decisions among TikTok Shop users in Makassar City. The study is motivated by the increasing competition in digital business and changes in consumer behavior, where consumers are increasingly active in conducting transactions through social commerce platforms. Promotional strategies such as discounts and free shipping are considered effective in attracting consumer attention and increasing purchase intentions quickly. This research employed a quantitative approach using a survey method by distributing questionnaires to 200 respondents who had made purchases on TikTok Shop. The research data were analyzed using SmartPLS software to determine the relationship between research variables. The results showed that discounts had a positive and significant effect on purchasing decisions with a t-statistic value of 5.876 and a p-value of 0.000. Free shipping also had a positive and significant effect on purchasing decisions with a t-statistic value of 4.952 and a p-value of 0.000. The R-Square value of 0.798 indicated that discounts and free shipping were able to explain purchasing decisions by 79.8%, while the remaining percentage was influenced by other variables outside this study. The findings indicate that price-based promotional strategies play an important role in increasing consumer purchasing decisions on the TikTok Shop platform and can be considered by business actors in determining effective and sustainable digital marketing strategies. This study also reveals that consumers tend to be more responsive to promotions that provide direct financial benefits compared to other promotional strategies. Discounts were found to be the most dominant variable influencing purchasing decisions because they create perceptions of more affordable prices and encourage consumers to make immediate purchases on digital platforms.